Eficiência do TIMSEN® nas etapas de escaldagem e préresfriamento em abatedouros de aves. - Souza, Edson Luiz de (2010)
Broiler production chain is very complex, and when compared with the chain of other domestic animals it has a much shorter cycle for obtainment of the final product (chicken meat and its derivatives), which like any other product from animal origin can be carrier of Foodbourne disease (FBD) causing agents. All stages of a production chain are important to obtain safe food, but some of them, due to their nature and complexity, need special care as they can compromise the product in a definite way, making it impossible to control the risks in the subsequent steps within the processing stages. The aim of this work was to evaluate the efficiency of TIMSEN® sanitizer (N-alkyl dimethyl benzyl ammonium 40% - Stabilized Urea 60%) when added to scalding and pre-chilling water in a poultry abattoir with official inspection in the South of Rio Grande do Sul. Scalding and pre-chilling water, as well as broiler carcasses after scalding and after chilling were sampled for evaluating the presence of Listeria monocytogenes, thermotolerant coliforms and for counting aerobic mesophilic microorganisms. TIMSEN® was efficient in the L. monocytogenes control when added to the scalding as well as pre-chilling water. It was also effective in the reduction of thermotolerant coliforms and aerobic mesophilic microorganisms.